PENERAPAN MODEL PEMBELAJARAN TENNIS VERBAL DALAM MENINGKATKAN MOTIVASI BELAJAR PPKn SISWA KELAS VIII SMP NEGERI 21 PEKANBARU - Windari, Windari; Erlinda, Sri; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was conducted with the aim to determine the effect of tennis verbal learning model in increasing the learning motivation of VIII grade students of SMP Negeri 21 Pekanbaru. This research is motivated by problems found in the learning process which are seen as phenomena that provide awareness for teachers to always provide innovations in the selection and use of models in the learning process. The tennis verbal learning model applies the verbal abilities of students in understanding PKn lessons that are communicated directly by students. The formulation of the problem in this study is